The mass media modernization resources in development of innovative economy (Путеводитель предпринимателя)
Implementation of the innovative scenario of development of economy is impossible without active participation of mass media. Owing to political, sociocultural, economic and other conditions the Russian mass media develop non-uniformly. In the Republic of Tatarstan there are active processes of creation of new business models of mass media, symbiosis of print and electronic media.